Histologic evaluation of activity and chronicity of lupus nephritis and its clinical significance - Sung-Eun Choi; Agnes B. Fogo; Beom Jin Lim (The Korean Society of Nephrology, 2023)
The National Institutes of Health (NIH) lupus nephritis activity and chronicity indices, which comprise six activity scores and four chronicity scores, have a long development history. The 2018 revised International Society of Nephrology/Renal Pathology Society classification for lupus nephritis adopted the most recent NIH indices to replace subclasses A, C, and A/C. Although an evidence-based approach should further evaluate the clinical significance of the modified NIH indices, recent validation studies demonstrated that the modified chronicity indices have a strong correlation with kidney outcome of lupus nephritis.